Effects of interval-based small-sided games on physiological responses and sprint performance in soccer players - Subarna, Subarna; Lovianti, Sheila Dwi; Arifin, Zaenal; Sofa, N. Siti Nura'eni; Nugraha, Angga; Marbun, Sandra Jaganda; Kusnadi, Nanang; Németh, Zsolt (Universitas Tanjungpura, 2026)
Background Mini-soccer games combine soccer-specific technical and tactical activities with high-intensity conditioning. However, evidence regarding physiological adaptations and sprint performance resulting from structured interval training among young Indonesian soccer players remains limited. Objectives To examine changes in aerobic fitness, resting and exercise heart rate, and 30-m sprint performance after an eight-week interval-based small-sided game (SSG) program in male under-17 soccer players. Methods Twenty-four PERSES Sumedang U-17 players (age 16.5 ± 0.6 years) completed a one-group pretest–posttest study. Training comprised 4 vs. 4 games on a 30 × 25 m pitch, performed as four 4-min bouts separated by 2-min passive recovery, three times weekly for eight weeks. Maximal oxygen uptake (VO₂max) was estimated using the Yo-Yo Intermittent Recovery Test Level 1; resting and exercise heart rate were recorded with Polar monitors; and 30-m sprint time was measured with electronic timing gates. Pre–post differences were assessed with paired-samples t tests (α = .05), and standardized paired effect sizes (dᶻ) were derived from the reported t statistics. Results VO₂max increased from 49.82 ± 2.91 to 54.73 ± 3.08 mL·kg⁻¹·min⁻¹ (mean change 4.91; 9.86%; t = 9.62; p < .001; dᶻ = 1.96). Resting heart rate decreased from 72.13 ± 4.87 to 67.08 ± 4.12 beats·min⁻¹ (−5.05; −7.00%; t = 7.44; p < .001; dᶻ = 1.52), and exercise heart rate decreased from 184.46 ± 5.72 to 178.25 ± 4.89 beats·min⁻¹ (−6.21; −3.37%; t = 8.17; p < .001; dᶻ = 1.67). Sprint time improved from 4.82 ± 0.19 to 4.56 ± 0.17 s (−0.26; −5.39%; t = 8.74; p < .001; dᶻ = 1.78). Conclusion Significant improvements were observed in all outcome parameters before and after the interval-based SSG program. The protocol may serve as a practical, soccer-specific physical training option for young players.